2000
DOI: 10.1097/00000478-200008000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Predominance Hodgkin's Disease

Abstract: Distinction of lymphocyte predominance Hodgkin's disease (LPHD) from other forms of lymphoma often requires immunohistochemistry (IHC). Most previously published recommended panels include markers to define the large neoplastic cells (for example, CD20, J chain, CD45) as well as the non-neoplastic background cells (CD21, CD45RO, CD57, TiA 1). In the present study we examine the practical use of a double IHC method designed to look simultaneously at two germinal center specific cell types: bcl6+ cells and [bc16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…However, THRLBCL-like NLPHL was not included in the analysis, nor in other studies, which aimed to identify differentially expressed markers between the two entities [30] , [31] , [32] , [33] . So far, many commonly expressed genes in tumor cells of both entities were identified, such as BCL6, CD75, EMA, J-chain and PU.1, as well as a typical kappa light chain restriction [11] , [34] , [35] , [36] , [37] . The only investigations which clearly point to a distinct pathogenesis of both diseases are two comparative genomic hybridization studies, in which a higher number and different genomic aberrations were identified in NLPHL than in THRLBCL [38] , [39] .…”
Section: Discussionmentioning
confidence: 99%
“…However, THRLBCL-like NLPHL was not included in the analysis, nor in other studies, which aimed to identify differentially expressed markers between the two entities [30] , [31] , [32] , [33] . So far, many commonly expressed genes in tumor cells of both entities were identified, such as BCL6, CD75, EMA, J-chain and PU.1, as well as a typical kappa light chain restriction [11] , [34] , [35] , [36] , [37] . The only investigations which clearly point to a distinct pathogenesis of both diseases are two comparative genomic hybridization studies, in which a higher number and different genomic aberrations were identified in NLPHL than in THRLBCL [38] , [39] .…”
Section: Discussionmentioning
confidence: 99%
“…After double staining with these antibodies, the authors observed that in cases of LPNHD they observed bcl-6-positive large cells rimmed by a number of CD57+ cells including Bcl6+ and CD57+ copositive cells. This appearance was highly specific for NLPHD as in PTGC this appearance was not seen and on double staining few CD57+ cells with very rare double-positive cells were seen [15]. …”
Section: Discussionmentioning
confidence: 99%
“…The characteristic lymphocyte-Predominant (LP) cells exhibit a GC phenotypic profile with expression of GC markers such as BCL6 [11, 21], GCET1 [22] and LMO2 [23], together with expression of transcription factors related to a sustained B cell program such as Oct-2 and BOB.1. Interestingly, the GC-related profile is seen not only in LP cells but also in the surrounding T cells, which characteristically create a rosette-like pattern typical of NLPHL (Figure 1).…”
Section: Nlphl: Usefulness Of the Microenvironment In Diagnosismentioning
confidence: 99%
“…Interestingly, the GC-related profile is seen not only in LP cells but also in the surrounding T cells, which characteristically create a rosette-like pattern typical of NLPHL (Figure 1). These rosetting T cells have a Follicular T cell phenotype with expression of CD3/CD4/CD57 [24], bcl6 [21], PD1 [20, 25] and, interestingly, CXCL13, a chemokine that is known to induce B cell homing to lymphoid follicles and that plays a role in the T cell-dependent B cell affinity maturation process [26]. These observations suggest that NLPHL is characterized by a GC phenotype in both LP and T cells.…”
Section: Nlphl: Usefulness Of the Microenvironment In Diagnosismentioning
confidence: 99%